Answer:
this should help XD
Explanation:
et's solve your equation step-by-step.
√2x−3+3=x
Step 1: Add -3 to both sides.
√2x−3+3+−3=x+−3
√2x−3=x−3
Step 2: Solve Square Root.
√2x−3=x−3
2x−3=(x−3)2(Square both sides)
2x−3=x2−6x+9
2x−3−(x2−6x+9)=x2−6x+9−(x2−6x+9)(Subtract x^2-6x+9 from both sides)
−x2+8x−12=0
(−x+2)(x−6)=0(Factor left side of equation)
−x+2=0 or x−6=0(Set factors equal to 0)
x=2 or x=6
Check answers. (Plug them in to make sure they work.)
x=2(Doesn't work in original equation)
x=6(Works in original equation)